2017
DOI: 10.1051/sicotj/2017016
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal allograft transplantation: a meta-analysis

Abstract: Purpose: This meta-analysis evaluates the mid- to long-term survival outcome of MAT (meniscal allograft transplantation). Potential prognosticators, with particular focus on chondral status and age of the patient at the time of transplantation, were also analysed. Study design: Meta-analysis. Methods: An online database search was performed using following search string: “meniscal allograft transplantation” and “outcome”. A total of 65 articles were analysed for a total of 3157 performed MAT with a mean follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 74 publications
(233 reference statements)
0
49
1
1
Order By: Relevance
“…Not only the surgical technique has been improved by the arthroscopic MAT, but also indications, patient selection, and postoperative rehabilitation have been improved during 30 years of clinical experience. Short- and long-term outcomes of both open and arthroscopic MAT have shown positive results in terms of pain relief and functional improvement [ 3 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only the surgical technique has been improved by the arthroscopic MAT, but also indications, patient selection, and postoperative rehabilitation have been improved during 30 years of clinical experience. Short- and long-term outcomes of both open and arthroscopic MAT have shown positive results in terms of pain relief and functional improvement [ 3 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…42 Age has been associated with reduced graft survivorship 26,34,46 and some authors consider it a negative prognostic factor. 3 On the other hand, no studies showed an association with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified areas in which there is need for more and better quality evidence, specifically concerning the role of preoperative chondral damage, sport level, time from meniscectomy, and smoking status, whose impact on clinical outcome is still controversial. Several systematic reviews and meta-analyses have been published in the last decade about MAT; these, however, were mostly introductory in their nature, [7][8][9][10][11][12] focused primarily on outcomes in general, 2,3,13,14 or evaluated one single predictor in detail, such as laterality, 15 the impact of concomitant procedures, 16 or the type of graft fixation. 17 Other reviewers considered particular aspects, such as the chondroprotective role of MAT 5 or the feasibility of sports activity after recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations